Analysis Capability Process of Fuel Tank Production: A Case Study in Manufacturing Industry - Fernando, Very; Setiawan, Indra; Rizki, Yulizan; Hardi Purba, Humiras; Nurul Azizah, Fahriza; Iskandar, Isdaryanto (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
The competition in the automotive industry is increasingly challenging, where the company's task of ensuring customers are satisfied with the products we produce is the main factor in winning them. That is the value of the manufacturing industry to continuously improve quality. This study aims to reduce the reject rate and determine the priority of problems in the fuel tank production process. This study uses the six sigma method based on a simple problem-solving methodology consisting of Define, Measure, Analyze, Improve and Control. This method combines various statistical tools and other process improvement approaches. The results of this study show that the company's Sigma level in February carried out in the welding & press section obtained a sigma value of 4.0 and process capability of 1.34. This means that the quality control process that has been carried out has not been going well because the product is defective and still needs to be improved. Finally, this paper provides some recommendations for improving process capability.